An audit of "do not attempt resuscitation" decisions in two district general hospitals: do current guidelines need changing?. Issue 976 (16th February 2007) - Harris, Dylan; Davies, Rachel
Abstract : Introduction: Doctors in all specialties are involved in making "do not attempt resuscitation" (DNAR) decisions; this can be a difficult and challenging process. Guidelines exist to provide an ethical and legal framework for the process and documentation of these decisions. Objective: To audit the documentation of resuscitation decisions in a sample of medical inpatients from two district general hospitals. Method: A retrospective case note audit of 50 medical inpatients, in which a DNAR decision had been made (28 from hospital 1, 22 from hospital 2). Results: Average age was 78.9 years (48% male:52% female). In both hospitals DNAR decisions were usually discussed with relatives (84%), documented in nursing notes (100%) and made by senior team members (90%). Although the decision was usually dated and clearly documented (98%), abbreviations were commonly used in hospital 2 (45.5% vs 0% in hospital 1, p<0.05). Decisions regarding other treatment were not consistently documented (78.6% and 72.7%, respectively) and there was little evidence that decisions were reviewed (14.3% and 31.8%). The decision was rarely discussed with the patient (6% of all patients), although 66% of patients were not in a position to have a discussion. Conclusions: Specific forms for recording DNAR decisions improve the clarity of documentation. Current recommendations to discuss resuscitation with patients are controversial and not followed. However, many patients are not in a position to hold a discussion when the need arises and the guidelines should advocate early discussion during a hospital admission in patients where this is appropriate, prior discussion with family and/or wider use of advanced directives.